Mobile-Based Nearby Mosque Determination System Application Using Particle Swarm Optimization (PSO) Algorithm In the Gayungan District - Budi Santoso; Wiwiet Herulambang; M Mahaputra Putra (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
Public facilities related to religion one of which is the mosque. Mosque Is a place of worship for Muslimsworldwide. The city of Surabaya which incidentally is a tourist city that is often visited by foreign and local tourists,and especially the Muslims who want to establish prayer and need access to the location of the nearest mosque. Thereal condition that often happens is that tourists do not know the position of the closest mosque around them, so spendtime searching for the existence of the mosque. Particle Swarm Optimization Method is an algorithm that is inspiredby the behavior of a group of birds in a group to look for food. This method is one of the methods for searching theshortest distance. With this method, it can provide solutions to produce the closest location. From the tests carriedout, the Particle Swarm Optimization algorithm has been successfully applied to the search for the nearest Mosquelocation point and has successfully designed and built a nearby Mosque location search application based on AndroidMobile. By comparing with the euclidean distance algorithm the results of Particle Swarm Optimization show that70% accurately show the same results.